ISOLASI SENYAWA AKTIF DARI LABAN (VITEX PINNATA) TUMBUHAN OBAT ASLI KALIMANTAN TIMUR DAN KALIMANTAN UTARA SEBAGAI BAHAN KOSMETIK - Purba, Ritson; Azizah, Amanda Salwa Nur; Maulidawati, Rista (PROSIDING SEMINAR NASIONAL KIMIA; Vol 3 No 1 (2024): Prosiding SNK 2024, 2024)
Laban ( Vitex pinnata ), a natural medicinal plant of East and North Kalimantan, was the subject of an isolation process to produce active chemicals. This study uses a chromatography column with a solvent gradient system to carry out the fractionation or isolation process. The crude plant extract is first fractionated using a solvent with the least polarity, n-hexane, and then additional solvent is added. The goal is to ascertain the anti-bacterial and antioxidant activity of plant isolates as well as obtain pure compounds and describe the properties and structure of isolated compounds. Previously, an extract known as Laban ( Vitex pinnata ) extract was utilized. This plant was isolated, and the isolation yield for Laban ( Vitex pinnata ) was 85.06%. The chromotography column for Vitex pinnata is done by mixing a sample of 10 grams of Vitex pinnata leaf extract with a 37.5 gram sample of silica and then inserting it into the saturated chromotography column. The isolates were tested for their antioxidant activity and anti-bacterial P.acne (anti-acne). Test of antioxidant were determined by their antioxidant activity through the DPPH free reduction mechanism with 3 repetitions control. The test was using a UV-Vis spectrophotometer at a temperature of 25°C with a wavelength of 514 μm.   Keywords: isolation, antioxidant, P.acne bacteria, cosmetics.